Screening of bacterial endophytes as potential biocontrol agents against soybean diseases - de Almeida Lopes, Karla Bianca (2018)
Aims: This research was aimed at identifying and characterizing endophytic micro-organisms associated with soybean that have antimicrobial activity towards soybean pathogens. Methods and Results: Soybean plants were collected from field trials in four locations of southern Brazil that were cultivated with conventional (C) and transgenic glyphosate-resistant (GR) soybeans. Endophytic bacteria isolated from roots, stems and leaves of soybeans were evaluated for their capacity to inhibit fungal and bacterial plant pathogens and 13 micro-organisms were identified with antagonistic activity. Approximately 230 bacteria were isolated and identified based on the 16S rRNA and rpoN gene sequences. Bacteria isolated from conventional and transgenic soybeans were significantly different not only in population diversity but also in their antagonistic capacity. Thirteen isolates showed in vitro antagonism against Sclerotinia sclerotiorum, Phomopsis sojae and Rhizoctonia solani. Bacillus sp. and Burkholderia sp. were the most effective isolates in controlling bacterial and fungal pathogens in vitro. Extracts and precipitates from culture supernatants of isolates showed different patterns of inhibitory activity on growth of fungal and bacterial pathogens. Conclusions: Bacillus sp. and Burkholderia sp. were the most effective isolates in controlling fungal pathogens in vitro, and the activity is mainly due to peptides. However, most of the studied bacteria showed the presence of antimicrobial compounds in the culture supernatant, either peptides, bacteriocins or secondary metabolites. Significance and Impact of the Study: These results could be significant to develop tools for the biological control of soybean diseases. The work brought to the identification of micro-organisms such as Bacillus sp. and Burkholderia sp. that have the potential to protect crops in order to enhance a sustainable management system of crops. Furthermore, the study provides the first evidences of the influence of management as well as the genetics of glyphosate-resistant soybean on the diversity of bacterial endophytes of soybean phytobiome.